Supplementation of Fermented Moringa Leaf Powder (Moringa oleifera) on Feed Consumption, Egg Weight and Feed Conversion Ratio (FCR) in Laying Duck - Pramestya, Ninda Rubi; Hidanah, Sri; Lamid, Mirni; Soepranianondo, Koesnoto; Lokapirnasari, Widya Paramita; Al-Arif, Mohammad Anam; Soeharsono, Soeharsono (Jurnal Medik Veteriner, 2021)
This study aimed to determine the effect of the addition of fermented moringa leaf powder on feed consumption, egg weight, Feed Conversion Ratio (FCR) of laying ducks. 60 laying ducks were randomized into four treatments i.e. (P0) 0% Moringa leaf powder fermentation, (P1) 0.5% Moringa leaf powder fermentation, (P2) 1% Moringa leaf powder fermentation, and (P3) 1.5% Moringa leaf fermentation. Treatment of concentration refered in 100% commercial feed for 3 weeks. The results showed that the adding of Moringa leaf powder fermentation to feed consumption in each treatment showed significantly different results (p <0.05) in each treatment, with the highest consumption at P2 (176.21 ± 0.92) and the lowest at P0 (158.21 ± 1.07). The results of the study on duck egg weight showed that P1, P2, P3 were significantly different with P0. The highest egg weight in P2 is (70.50 ± 0.34) and the lowest is P0 (66.98a ± 0.29). FCR of laying duck in each treatment showed significantly different results in each treatment, with the highest at P0 (3,81± 0,34) and the lowest at P2 (3,27 ± 0,09). In conclusion, the addition of 1% Moringa leaf powder in 100% of commercial feed can increase feed consumption, increase egg weight and decrease FCR.